Application and Perceived Benefits of AI Literacy: A Phenomenological Study in Academic Librarianship - Kayode, Adeniyi Isaiah; Eromosele , George Osas; Oguntayo , Sunday Adebisi (Inkunabula: Journal of Library Science and Islamic Information, 2026)
This study investigates how artificial intelligence (AI) literacy is applied and perceived by academic librarians in university libraries across Kwara State, Nigeria. Employing a phenomenological approach, fifteen academic librarians were interviewed to explore their lived experiences in utilizing AI-related tools and services. The findings reveal that AI literacy is practiced through various technologies, including virtual assistants, research platforms, chatbots, and discovery engines, which enhance access to scholarly resources and improve library service delivery. However, several challenges hinder effective adoption, such as limited funding, inadequate professional training, ethical concerns, and insufficient Internet infrastructure. The study concludes that although AI literacy provides significant benefits for academic library services, its successful integration requires strategic planning, strong institutional support, and appropriate ethical governance. This research contributes to the literature by situating AI literacy within the lived experiences of academic librarians in a developing-country context, offering new insights into both the opportunities and the constraints of AI adoption in university libraries.